Has the prevalence of asthma increased in children? Evidence from a long term study in Israel. Issue 3 (June 1997) - Goren, A I; Hellmann, S
Abstract : BACKGROUND: The permit to build and operate the first 1400 megawatt coal fired power plant in Israel was given provided that three monitoring systems-environmental, agricultural, and health monitoring-be set up near the plant. This study was carried out in the framework of a health monitoring system which included a mortality survey, requests for health services, a schoolchildren's health survey, and an adult panel study. METHODS: 2nd, 5th, and 8th grade school-children living in three communities with different expected levels of air pollution were followed up every three years. They performed pulmonary function tests (PFT), and their parents filled out American Thoracic Society-National Heart and Lung Institute (ATS-NHLI) health questionnaires. A follow up of the prevalence of respiratory conditions among the studied schoolchildren in four rounds of tests was carried out. This report deals with the changes in the prevalence of asthma, related respiratory conditions, and PFT in the data sets gathered among 5th grade schoolchildren. RESULTS: A significant (p = 0.0024) increase in the prevalence of asthma could be observed among 5th grade children in all three communities studied between 1980 and 1989. At the same time a significant (p = 0.0172) rise in the prevalence of wheezing accompanied by shortness of breath could be observed. A similar trend could not be found for the prevalence of bronchitis and other respiratory conditions among the studied children. PFT (FEV1, FEV1/FVC) of children suffering from asthma or from wheeze accompanied by shortness of breath were lower than those of healthy children. Changes in the prevalence of background variables over time could not explain the significant rise in the prevalence of asthma among the children. CONCLUSIONS: The significant rise in asthma and related respiratory conditions coupled with reduced PFT observed in this study suggest that the increase over time in the prevalence of asthma is a true increase in morbidity and not due to reporting bias. The increased prevalence of asthma could be observed in all the communities studied and does not seem to be connected with the operation of the power plant.